High performance fiber reinforced cement composites 2 (HPFRCC 2) : proceedings of the second International Workshop "High Performance Fiber Reinforced Cement Composites", Ann Arbor, USA, June 11-14, 1995 - Naaman, Antoine E.; Reihardt, H. W. (Hans Wolfgang) 1931- (RILEM proceedings, 1996)
The leading international authorities bring together in this contributed volume the latest research and current thinking on advanced fiber reinforced cement composites. Under rigorous editorial control, 13 chapters map out the key properties and behaviour of these materials, which promise to extend their applications into many more areas in the coming years.